Shadow's edge - Weeks, Brent (New York Orbit, 2008)
Kylar has rejected the assassin's life in the wake of the Godking's violent coup, but when he learns that Logan Gyre, heir to Cenaria's throne, might be alive, trapped and in hiding, Kylar faces an impossible choice.
Includes "extras", including Meet the Author and an excerpt of the author's next book (p. [637]-645)
113908
Keywords: Stern, Kylar (Fictitious character) -- Fiction; Assassins -- Fiction; Imaginary places -- Fiction; Oregon authors; Fantasy fiction; Fiction